NArCoS: The new hodoscope for neutrons and charged particles - Pagano, E. V.; De Filippo, E.; Russotto, P.; Cardella, G.; Castoldi, A.; Geraci, E.; Gnoffo, B.; Guazzoni, C.; Lanzalone, G.; Maiolino, C.; Martorana, N. S.; Pagano, A.; et al. (Frontiers in Physics, 2023)
Proper detection of neutrons and charged particles is motivated by the recent efforts to construct new facilities for radioactive ion beams (RIBs) worldwide. Detection of neutrons is an important opportunity to improve our understanding of nuclear spectroscopy and reaction dynamics, with the possibility of constraining theoretical models of the nuclear equation of state (NEoS) and investigating in-medium nuclear interactions. This topic also has important implications in the study of astrophysical objects, such as neutron stars. In this work, the state-of-the-art of Neutron Array for Correlation Studies (NArCoS), a new hodoscope for neutron and charged particles under construction in Catania (INFN), is briefly reviewed.